Bacteriological studies for Kranji catchment - Lee, Li Jun. (2009)
In the near future, Singapore plans to revamp Kranji Reservoir and to re-open its tropical wetland to public recreational activities. However, water quality of the reservoir has to meet the standards of World Health Organization (WHO) water qualities in recreational use. This is because polluted waters will cause serious illnesses like gastrointestinal diseases. Bacteriological study was conducted previously, led by a project team from School of Civil and Environmental Engineering (CEE) of Nanyang Technological University. In their past analysis of dry-weather water samples, it was concluded that CP02 had the highest concentration of coliform and enterococci. In this project, in-depth study of the bacteriological level in CP02 catchment was continued. In order to study the bacterial level, m-ColiBlue24® method and IDEXX Enterolert™ most-probable-number (MPN) method were conducted on the water samples. Results from this study found that the water quality in certain location of Peng Siang sub-catchment was close to that typical for raw sewage. The CP02 and its district had received total coliform load and fecal coliform load specifically E. coli from both point and non-point sources. However, it was unable to conclude that point source or non-point source was the major contributor to its poor water quality. In Neo Tiew, Kangkar, Tengah and Pang Sua sub-catchments, E. coli counts did not exceed 1x106 CFU/100ml. Peng Siang sub-catchment had the highest E. coli counts among all the sub-catchment where the farm and agricultural areas show a range of E. coli from 0 to 50x106 CFU/100ml and residential area show E. coli count of not exceeding 50x103 CFU/100ml. The undulating curve of 18 hours water sampling results also showed that there are human activities discharging wastewater in random intervals to CP02. There was poor stability of bacterial level in CP02 and both point and non-point sources pollution were noticeable. Few of the sources and types of pollutant were found inconclusive as there were insufficient sample size and field observations. However, it is evidential that better water management efforts are urgently needed, in order to stop further deterioration of its water quality.